Prediction of preterm labour from a single blood test: The role of the endocannabinoid system in predicting preterm birth in high-risk women. (December 2019) - Bachkangi, P.; Taylor, A.H.; Bari, Monica; Maccarrone, Mauro; Konje, Justin C.
Abstract: Objective: To determine if plasma concentrations of the N -acylethanolamines (NAEs) N -arachidonoylethanolamine (AEA), N -oleoylethanolamide (OEA) and N -palmitoylethanolamide (PEA) increase in women at high risk for preterm birth (PTB) and whether these could be used to predict preterm delivery and if so, how they compare with current methods. Design: Prospective cohort study. Setting: A large UK teaching hospital. Population: 217 pregnant women were recruited between 24 and 34 gestational weeks at 'high-risk' for PTB, recruited from a prematurity prevention clinic or antenatal wards. Methods: Plasma AEA, OEA, and PEA concentrations were measured using ultra-high performance liquid chromatography-tandem mass spectrometry whilst FAAH enzyme activity was measured by fluorometric radiometric assay and CL by ultrasound scan. The clinical usefulness of these measurements were determined by ROC and multivariate analyses. Results: AEA and PEA concentrations were significantly higher in women who delivered prematurely. An AEA concentration >1.095 nM predicted PTB, the gestational age at delivery and the recruitment to delivery interval (RTDI). A PEA concentration >17.50 nM only predicted PTB; FAAH enzyme activity was not related to these changes. Multivariate analysis (all variables) generated an equation to accurately predict the RTDI. Conclusions: A single plasma AEA or PEA measurement can predict PTB. A single AEA measurement predicts the gestational age of delivery and the remaining period of pregnancy with reasonable accuracy and better than existing conventional tests thus offering a better window for primary prevention of PTB.